High-power and low-loss LiZn microwave ferrite material and preparation method thereof
By introducing NiO and CuO into LiZn ferrite materials to form a composite system and using Bi2O3, CaCO3 and Co2O3 dopants to optimize the preparation process, the problem of low loss and high power compatibility of LiZn ferrite materials was solved, and the fabrication of high-performance microwave devices was realized.
Patent Information
- Application Number
- CN202511695887.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2025-12-19
- Estimated Expiration
- 2045-11-19
AI Technical Summary
Existing LiZn ferrite materials have high ferromagnetic resonance linewidth and dielectric loss, making it difficult to simultaneously achieve low loss and high power, thus failing to meet the high-performance requirements of 5G base stations and phased array radar systems.
By introducing NiO and CuO to form a Li-Zn-Ni-Cu quaternary composite ferrite system, and combining it with Bi2O3, CaCO3 and Co2O3 dopants, a two-step ball milling and post-doping process is adopted to optimize the material formulation and microstructure, reduce the ferromagnetic resonance linewidth and dielectric loss, and improve the spin wave linewidth.
We have successfully fabricated LiZn microwave ferrite materials with high Curie temperature, low ferromagnetic resonance linewidth, low dielectric loss, and high spin wave linewidth to meet the high-performance requirements of 5G base stations and phased array radar systems, reduce device insertion loss, and improve power handling capability.
Smart Images

Figure CN121159243A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of electronic materials, and particularly relates to a high-power and low-loss LiZn microwave ferrite material and a preparation method thereof. BACKGROUND
[0002] There are two important development directions of radar, satellite and communication equipment electronic systems: low power consumption and over-the-horizon transmission and reception. Circulators and phase shifters are key components of a large number of transceiver unit antennas in 5G base stations and phased array radar systems, and play a crucial role in the entire system. Microwave ferrite materials are the core factors of microwave ferrite devices such as circulators and phase shifters, which determine the performance of the devices in terms of bandwidth, insertion loss, isolation and high power bearing capacity. Therefore, in order to achieve the goal of low power consumption and over-the-horizon transmission and reception, it is necessary to reduce the insertion loss of circulators / phase shifters and at the same time improve their power bearing capacity. This requires microwave ferrite materials to have low ferromagnetic resonance line width (ΔH H ), low dielectric loss (tan δ ε ) and high spin wave line width (Qs H k ), which is also the current research hotspot and trend of microwave ferrite technology.
[0003] LiZn ferrite has the characteristics of wide adjustable range of saturation magnetization, high Curie temperature and good squareness, but its ferromagnetic resonance line width and dielectric loss are relatively high, resulting in high insertion loss of the device; and the spin wave line width is small, which is difficult to bear high power. The ferromagnetic resonance line width and the spin wave line width are mutually restrictive technical bottlenecks, and low loss and high power are difficult to simultaneously meet the performance indicators.
[0004] In the prior art, ferrite is basically prepared based on Li-Zn-Ti, but Li ions are easy to volatilize during high-temperature sintering. In order to reduce the problem of easy volatilization of Li ions at high temperature, Bi2O3 is usually added as a low-temperature sintering aid to reduce the sintering temperature, for example, application No. 202410208567.1, but the saturation magnetization of the product is =3900Gs±3%, which belongs to the medium level, limiting the application of high power; the Curie temperature Tc>300℃, which can only meet the demand of conventional communication equipment (working temperature -40~85℃), and the magnetic performance will significantly decay (such as 4πMs linearly decreases with temperature rise) under high temperature environment, which cannot adapt to high temperature working environment.
[0005] In order to meet the high power and low insertion loss requirements of circulators / phase shifters for 5G base stations and phased array radars, how to prepare LiZn ferrite with excellent electromagnetic properties such as high Curie temperature, high spin wave linewidth, low ferromagnetic resonance linewidth and low dielectric loss is of great significance for reducing the insertion loss of microwave ferrite devices and improving the power bearing capacity. SUMMARY
[0006] The technical problem to be solved by the present application is to overcome the shortcomings of the prior art and provide a high-power and low-loss LiZn microwave ferrite material and a preparation method.
[0007] To solve the above technical problems, the core idea of the present application is that low loss is mainly realized by reducing dielectric loss and ferromagnetic resonance linewidth, wherein the dielectric loss is closely related to the content of Fe 2+ ions in the material, and the generation of Fe 2+ can be effectively inhibited by iron deficiency in the formula, thereby reducing the dielectric loss; and the ferromagnetic resonance linewidth is mainly affected by intrinsic linewidth, surface roughness, magnetic crystal anisotropy, pores and other factors, and the ferromagnetic resonance linewidth can be effectively reduced by increasing the material density and reducing the magnetic crystal anisotropy constant; high power requires that the material has a high spin wave linewidth, which can be improved by refining the grain size and adding fast relaxation ions. The present application combines systematic technical innovations in material formula design, microstructure regulation and magnetic and dielectric performance coupling optimization, and breaks through the long-term technical bottleneck that low-loss and high-power ferrite materials are difficult to achieve.
[0008] The technical scheme provided by the present application is: A high-power and low-loss LiZn microwave ferrite material, which has a spin wave linewidth H k >17Oe; the raw materials thereof include main materials and dopants, the main materials include Li2CO3, ZnO, MnCO3, CuO, NiO and Fe2O3; and the dopants include Bi2O3, CaCO3 and Co2O3.
[0009] Further, the main materials include 8.7-14.1 mol% Li2CO3, 3.4-15.1 mol% ZnO, 2.8-3.6 mol% MnCO3, 0.3-1.2 mol% CuO, 1.8-10.4 mol% NiO and 65.3-75.5 mol% Fe2O3 in terms of molar percentage.
[0010] The present application creatively introduces NiO and CuO into the main formula of LiZn ferrite, forming a Li-Zn-Ni-Cu quaternary composite ferrite system, and the introduction of Ni helps to reduce the magnetic crystal anisotropy constant, thereby reducing the ferromagnetic resonance linewidth H ), and realizes low loss; the introduction of Cu can reduce sintering temperature, promote densification, reduce pores, and cooperate with NiO in the LiZn matrix, which not only helps to reduce H the spin wave width; meanwhile, the main component is still LiZn, which ensures that the material still has the inherent advantage of high Curie temperature (Tc > 420℃). T c
[0011] Further, the dopant includes 0.05~0.30wt% Bi2O3, 0.05~0.25wt% CaCO3 and 0.0025~0.01wt% Co2O3 in the main material in terms of molar percentage.
[0012] In the dopant adopted by the application, Bi2O3 is a low-temperature sintering aid, which can form a liquid phase, greatly promote grain growth and densification, thereby reduce porosity, reduce H ; CaCO3 can refine the grain, improve the grain boundary resistivity, and significantly reduce the dielectric loss; the cobalt ion in Co2O3 is a "fast relaxation ion", which can effectively increase the magnetic crystal anisotropy field, thereby greatly improve the spin wave width (ΔHk > 1000 Oe) H k , which is the key to realize high power capacity.
[0013] The three dopants are selected and their proportions are accurately controlled, and they cooperate with each other to improve the performance of the material.
[0014] Further, the raw material further includes an organic binder, the organic binder is PVA, and the addition amount is 10~20% of the total mass of the main material and the dopant.
[0015] Based on the overall inventive concept, the application further provides a preparation method of the high-power, low-loss LiZn microwave ferrite material. (1) primary ball milling and pre-sintering of the main material to obtain pre-sintered powder; (2) adding a dopant to the pre-sintered powder and performing secondary ball milling; (3) adding an organic binder to the secondary ball milling material after step (2) to granulate and press into a blank; (4) sintering the blank to obtain the high-power, low-loss LiZn microwave ferrite material.
[0016] Further, in step (1), the rotation speed of ball milling is 200~400 rpm, and the ball milling time is 3~6h.
[0017] Furthermore, in step (1), the pre-firing temperature is 830~920℃ and the pre-firing time is 2~4h.
[0018] Furthermore, in step (2), the rotation speed of the secondary ball mill is 200~400 rpm, and the time is 4~8h.
[0019] Furthermore, in step (3), the molding pressure is 80~150MPa and the holding pressure is 20~50s.
[0020] Furthermore, in step (4), the sintering temperature is 1000~1120℃, and the sintering holding time is 2~6h.
[0021] In the preparation method of this invention, a two-step ball milling method is adopted, which involves ball milling and pre-calcination to ensure that the main materials are fully mixed and undergo solid-phase reaction to generate the desired ferrite phase. After adding the dopant, a second ball milling is performed to uniformly disperse the dopant into the pre-calcined powder and effectively refine the grain size. This step-by-step ball milling process ensures high uniformity of composition and ideal microstructure.
[0022] In the preparation method of the present invention, the doping step is placed after pre-calcination and before secondary ball milling, rather than at the beginning. On the one hand, this can avoid the possibility that low-melting-point substances such as Bi2O3 may volatilize or become ineffective during the pre-calcination process if added too early. On the other hand, this order of addition can ensure that the dopant mainly acts on the grain boundaries, so as to better exert its modifying effect without affecting the formation of the main crystalline phase.
[0023] In the preparation method of the present invention, a relatively low sintering temperature (1000~1120℃) and a suitable holding time (2~6h) are selected, which can ensure that the dopant can play a role in assisting sintering and achieving densification, while preventing excessive grain growth.
[0024] Compared with the prior art, the advantages of the present invention are as follows: (1) This invention, through a specific Li-Zn-Ni-Cu main component system and Bi-Ca-Co composite dopant formulation, employs a "two-step ball milling" and "post-doping" preparation process to ensure uniform composition and refined grains, ultimately producing a high Curie temperature ( ). T c >420℃), low ferromagnetic resonance linewidth ( H <270 Oe), low dielectric loss (tan tan ) δ ε <5×10 -4 ) and high spin linewidth ( H kThe LiZn microwave ferrite material with a high saturation magnetization (4.17 emu / g) and a low coercive force (17 Oe) meets the urgent demand of high-performance microwave devices for 5G and phased array radars.
[0025] (2) The microwave circulator, phase shifter and other devices prepared from the high-power and low-loss LiZn microwave ferrite material according to the application can simultaneously realize low insertion loss and high power bearing capacity, which will help to reduce the overall power consumption of 5G base stations and phased array radar systems, prolong the service life of the devices, and significantly improve the reliability of over-the-horizon transmission and reception, and has great significance for promoting the development of advanced communication and radar technologies.
[0026] (3) The preparation method according to the application adopts a traditional solid-phase method process route, does not need special or expensive equipment, the production process flow is stable, the parameter control is clear, and the method is very suitable for large-scale industrial production, and has high market conversion prospects and economic benefit potential. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 The scanning electron microscope photo of the LiZn ferrite material of Example 4.
[0028] Figure 2 The scanning electron microscope photo of the LiZn ferrite material of Example 7.
[0029] Figure 3 The scanning electron microscope photo of the LiZn ferrite material of Example 12. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present application is not limited to the following specific embodiments.
[0031] Unless otherwise defined, all the professional terms used in the following are the same as those commonly understood by those skilled in the art. The professional terms used in the present application are only for the purpose of describing the specific embodiments, and are not intended to limit the scope of protection of the present application.
[0032] Unless otherwise specified, all the reagents and raw materials used in the present application are commercially available or can be prepared by known methods.
[0033] The performance of the LiZn microwave ferrite material below is as follows: saturation magnetization 4 πM s Curie temperature T c Tested by VSM-300 of Changchun Yingpu Magnetoelectric Technology Development Co., Ltd., ferromagnetic resonance line width HTested with DH811B of Beijing Dahua Radio Instrument Factory according to GB / T 9633-2012 standard at 9.25 GHz Φ 0.8mm small ball sample, dielectric constant ε 、 and dielectric loss tan δ ε Tested with DH406B of Beijing Dahua Radio Instrument Factory according to GB / T 9633-2012 standard at 9.25 GHz on round bar sample, spin wave line width ΔH k Tested with spin wave test system of Chengdu Enchi Microwave Technology Co., Ltd. according to GB / T 9633-2012 standard at 9.25 GHz Φ 0.6mm small ball sample.
[0034] Examples 1-4: The raw material components of the high-power, low-loss LiZn microwave ferrite material in Examples 1-4 are shown in Table 1.
[0035] Table 1 Raw material components of Examples 1-4
[0036] The preparation method of the high-power, low-loss LiZn microwave ferrite material in Examples 1-4 includes the following steps: (1) Li2CO3, ZnO, MnCO3, NiO, CuO and Fe2O3 are proportioned according to Table 1, ball milled at a speed of 300 rpm for 3 hours, uniformly mixed, then dried, and finally pre-fired at 850°C for 2.5h to obtain a primary pre-fired material; (2) 0.1wt% Bi2O3, 0.18wt% CaCO3 and 0.005wt% Co2O3 are added to the primary pre-fired material obtained in step (1), and the mixture is then ball milled at a speed of 300 rpm for 6h; (3) 15wt% organic binder PVA is added to the secondary ball milled material obtained in step (2) based on the total amount of the main material and dopant, granulated, and pressed into a blank (molding pressure is 120 MPa, holding pressure for 30s); (4) The blank is sintered at 1020°C for 2 hours to obtain a high-power, low-loss LiZn microwave ferrite material.
[0037] The performance test results of the LiZn microwave ferrite material in Examples 1-4 are shown in Table 2. Within the range of the proportions, as the Ni-Cu ratio increases, the ferromagnetic resonance line width decreases significantly, the spin wave line width increases slightly, and the dielectric loss also decreases slightly. The SEM photo of the LiZn microwave ferrite material prepared in Example 4 is as follows: Figure 1As shown, the crystal grains grow fully and uniformly, the grain porosity is basically eliminated, and the microstructure is relatively dense.
[0038] Table 2 Performance test results of LiZn microwave ferrite materials
[0039] Examples 5-8: The raw material components of the high-power and low-loss LiZn microwave ferrite materials in Examples 5-8 are shown in Table 3.
[0040] Table 3 Raw material components of Examples 5-8
[0041] The preparation method of the high-power and low-loss LiZn microwave ferrite materials in Examples 5-8 includes the following steps: (1) Li2CO3, ZnO, MnCO3, NiO, CuO and Fe2O3 are proportioned according to the proportions in Table 3, ball-milled for 3 hours at a rotation speed of 300 rpm, uniformly mixed, then dried, and finally pre-fired at 870°C for 2.5h to obtain a primary pre-fired material; (2) 0.15wt% Bi2O3, 0.18wt% CaCO3 and 0.005wt% Co2O3 are added to the primary pre-fired material obtained in step (1), and then the mixture is ball-milled for 6h at a rotation speed of 300 rpm; (3) 15wt% of an organic binder PVA is added to the secondary ball-milled material obtained in step (2) to granulate, and the granulated material is pressed into a green body (molding pressure is 120 MPa, and pressure holding time is 30s); (4) The green body is sintered at 1050°C for 3 hours to obtain a high-power and low-loss LiZn microwave ferrite material.
[0042] The performance test results of the LiZn microwave ferrite materials in Examples 5-8 are shown in Table 4, and the electromagnetic performance change trend is consistent with that of Examples 1-4. The SEM photo of the LiZn microwave ferrite material prepared in Example 7 is shown in Figure 2 As shown, the grain porosity is basically eliminated, and the microstructure is relatively dense.
[0043] Table 4 Performance test results of LiZn microwave ferrite materials
[0044] Examples 9-12: The raw material components of the high-power and low-loss LiZn microwave ferrite materials in Examples 9-12 are shown in Table 5.
[0045] Table 5 Main raw material components of Examples 9-12
[0046] The preparation method of the high-power and low-loss LiZn microwave ferrite material in Examples 9-12 comprises the following steps: (1) Li2CO3, ZnO, MnCO3, NiO, CuO and Fe2O3 are proportioned according to the proportions in Table 5, ball-milled at a rotation speed of 300 rpm for 3 hours, uniformly mixed, then dried, and finally pre-fired at 920°C for 3 hours to obtain a primary pre-fired material; (2) 0.3wt% Bi2O3, 0.15wt% CaCO3 and 0.012wt% Co2O3 are added to the primary pre-fired material obtained in step (1), and then the mixture is secondarily ball-milled at a rotation speed of 300 rpm for 6 hours; (3) 15wt% organic binder PVA is added to the secondarily ball-milled material obtained in step (2) accounting for 15wt% of the total amount of the main material and dopant, granulated, and pressed into a blank (molding pressure is 120 MPa, and pressure holding time is 30 seconds); (4) The blank is sintered at 1100°C for 3 hours to obtain a high-power and low-loss LiZn microwave ferrite material.
[0047] The performance test results of the LiZn microwave ferrite material in Examples 9-12 are shown in Table 6, and the electromagnetic performance change trend is consistent with that of Examples 1-4. The SEM photo of the LiZn microwave ferrite material prepared in Example 12 is shown in Figure 3 , the grain is small and uniform, and the microstructure is relatively dense.
[0048] Table 6 Performance test results of LiZn microwave ferrite material
[0049] Comparative Examples 1-3: Comparative Example 1 is mainly compared with Example 4, Comparative Example 2 is mainly compared with Example 7, and Comparative Example 3 is mainly compared with Example 12. The main raw material components of Comparative Examples 1-3 are shown in Table 7.
[0050] Table 7 Main raw material components of Comparative Examples 1-3
[0051] The preparation method of the LiZn microwave ferrite material in Comparative Examples 1-3 comprises the following steps: (1) Li2CO3, ZnO, MnCO3 and Fe2O3 are proportioned according to the proportions in Table 7, ball-milled at a rotation speed of 300 rpm for 3 hours, uniformly mixed, then dried, and finally pre-fired according to the requirements in Table 8 to obtain a primary pre-fired material; Table 8 Pre-burning conditions of Comparative Examples 1-3
[0052] (2) The first pre-burning material obtained in step (1) was doped with the dopants shown in Table 9, and then the mixture was secondarily ball-milled at 300 rpm for 6 h; Table 9 Dopant contents of Comparative Examples 1-3
[0053] (3) The secondarily ball-milled material obtained in step (2) was granulated by adding 15 wt% of organic binder PVA based on the total mass of the main material and the dopants, and then the granules were pressed into blanks (molding pressure: 120 MPa, pressure holding time: 30 s); (4) The blanks were sintered according to the conditions shown in Table 10 to obtain LiZn microwave ferrite materials.
[0054] Table 10 Sintering conditions of Comparative Examples 1-3
[0055] The performance test results of the LiZn microwave ferrite materials in Comparative Examples 1-3 are shown in Table 11. From the test data, it can be seen that the introduction of NiO and CuO into the LiZn ferrite can significantly reduce the ferromagnetic resonance line width, and at the same time increase the spin wave line width.
[0056] Table 11 Performance test results of LiZn microwave ferrite materials
[0057] The above is only a preferred embodiment of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation, or direct or indirect application in other related technical fields, which is made by using the content of the specification and drawings of the present application, is also included in the patent protection scope of the present application.
Claims
1. A high power, low loss LiZn microwave ferrite material characterized in that, Spin wave linewidth of the high power, low loss LiZn microwave ferrite material H k > 17Oe; The raw materials include main materials and dopants, the main materials include Li2CO3, ZnO, MnCO3, CuO, NiO and Fe2O3; the dopants include Bi2O3, CaCO3 and Co2O3.
2. The high power, low loss LiZn microwave ferrite material of claim 1, wherein, The main materials include 8.7~14.1mol% Li2CO3, 3.4~15.1mol% ZnO, 2.8~3.6mol% MnCO3, 0.3~1.2mol% CuO, 1.8~10.4mol% NiO and 65.3~75.5mol% Fe2O3 in terms of molar percentage.
3. The high power, low loss LiZn microwave ferrite material of claim 1, wherein, The dopants include 0.05~0.30wt% Bi2O3, 0.05~0.25wt% CaCO3 and 0.0025~0.01wt% Co2O3 in terms of molar percentage.
4. The high power, low loss LiZn microwave ferrite material of claim 1, wherein, The raw materials further include an organic binder, the organic binder is PVA, and the addition amount of the organic binder is 10~20% of the total mass of the main materials and the dopants.
5. A method of producing a high power, low loss LiZn microwave ferrite material as claimed in any one of claims 1 to 4, characterised in that, The method includes the following steps: (1) performing one-time ball milling and pre-sintering on the main materials to obtain pre-sintered powder; (2) adding the dopants to the pre-sintered powder and performing second-time ball milling; (3) adding the organic binder to the second-time ball-milled material after step (2) to perform granulation and press into a blank; (4) sintering the blank to obtain the high-power and low-loss LiZn microwave ferrite material.
6. The production method according to claim 5, wherein In step (1), the rotation speed of ball milling is 200~400 rpm, and the ball milling time is 3~6h.
7. The production method according to claim 5, wherein In step (1), the pre-sintering temperature is 830~920℃, and the pre-sintering time is 2~4h.
8. The production method according to claim 5, wherein In step (2), the rotation speed of second-time ball milling is 200~400 rpm, and the time is 4~8h.
9. The production method according to claim 5, wherein In step (3), the forming pressure is 80~150MPa, and the pressure maintaining time is 20~50s.
10. The production method according to claim 5, wherein In step (4), the sintering temperature is 1000~1120℃, and the sintering heat preservation time is 2~6h.
Citation Information
Patent Citations
BE678312A
Lithium-zinc ferrite electromagnetic wave absorption material and preparation method thereof
CN101255052A
Lithium ferrite material applied to C waveband phase shifter
CN101549993A
LiZn ferrite material for Ka-band phase shifter and preparation method thereof
CN102167575A
High-Q value nickel and zinc ferrite with initial permeability of 70 and preparation method thereof
CN102603280A
Cited By
X-band high-power lithium zinc ferrite material and preparation method thereof
CN122127143A
